The effect of 20% ethanol on liver enzymes activity and the protective efficacy of vitamins C, E,selenium and salymarin in rabbits - Dh, Abd Ali W.; Ibrahim, Selim S.; Shalan, M.J; Fouad, Ibrahim (Al-Mukhtar Journal of Sciences, 2008)
This study aimed at investigating the efficacy of vitamins (C and E), selenium and silymarin supplementation in reducing drastic effects of ethanol. Male rabbits were subdivided into three groups: The first was a control group, the second received balanced diet and daily 20% ethyl alcohol as drinking water, the third received the same diet and 20% alcohol and supplemented with a mixed dose of vitamin C (1 mg/100g body weight), Vitamin E (1 mg/ 100 g body weight), Selenium (0.01 mg/ 100 g body weight) and silymarin (1 mg/ 100 g body weight) daily by gastric tube. Blood samples were taken after 2,4,6 and 8 weeks of treatment. Significant ethanol-induced elevations in serum ALT, AST, ALP and LDH activities were observed. Combined treatment of alcohol-treated animals with Vitamins (C and E), selenium and silymarin enhanced marked improvement in the biochemical, physiological indicating their protective effects against toxic effects of ethanol